Geotechnical Design and Practice Selected Topics - Ilamparuthi, K.; Robinson, R. G. (Developments in Geotechnical Engineering,, 2019)
This book presents articles covering a wide spectrum of topics in geotechnical engineering, including properties of soils, unsaturated soil mechanics, ground improvement, liquefaction and seismic studies, soil-structure interaction and stability analysis of man-made and natural slopes. The contributing authors are renowned researchers in their respective fields, which include soft ground improvement, seismic response of retaining structure using soil-structure Interaction (SSI) principles, and unsaturated soils. Based on keynote addresses and invited talks presented at the Indian Geotechnical Conference 2016, this book will prove a valuable resource for practicing engineers and researchers in the field of geotechnical engineering.